Figure images in Artjamila's Artworks: an autism spectrum perspective/ Mumtaz Mokhtar, Wan Samiati Andriana WMD and Noorhashimah Mohamed Noordin - Mokhtar, Mumtaz; WMD, Wan Samiati Andriana; Mohamed Noordin, Noorhashimah (Universiti Teknologi MARA, Perak, 2023)
Children with autism have problems expressing themselves. One of these problems is communication. This communication disorder involves not only speech but also facial expressions and body movements. Yet children with autism can express themselves through drawing. Artjamila, or the full name Wan Jamila Wan Shaiful Bahri, is a child with autism who has extraordinary abilities which she tends to draw. Most of her drawings are based on interests, experiences, careful observation, and things that touch his heart. One of her abilities can be seen through the development of figure image in her artworks. The method of this study is a qualitative method with a case study of selected paintings. This approach has the intent to better understand the human figure artworks from an autism spectrum perspective. The data is collected from studio visit, gallery visits and observation of artefacts. By observing Artjamila's artwork of figure images there found 3 major phases in Jamila's development of the figure which are early phase which starts at 5 years old, elongation ability and towards maturity. In general, society often associates autism with the individual's deprivation and vulnerability to the environment or association. However, they are found to have creativity and thoroughness in doing things. The image of figure that was revealed succeeded in becoming an expression of the feelings and thoughts of the autistic painter, thus alleviating the explosion of silenced feelings.